The effects of the covid-19 pandemic on puberty: a cross-sectional, multicenter study from Turkey - Gul Yesiltepe Mutlu; Elif Eviz; Belma Haliloglu; Heves Kirmizibekmez; Fatma Dursun; Servan Ozalkak; Atilla Cayir; Beste Yuksel Sacli; Mehmet Nuri Ozbek; Huseyin Demirbilek; Sukru Hatun (BMC, 2022)
Abstract Backgrounds During the Coronavirus-19 disease (Covid-19) pandemic it was observed that the number of girls presenting with early puberty had increased. The aim of this study was to carry out a retrospective evaluation of the characteristics of girls who had been referred for evaluation of precocious puberty in five different pediatric endocrinology units, before and during the pandemic. Methods The study participants comprised 359 girls who were assigned into 2 groups a pre-pandemic group (n:214) and a pandemic group (n:145). Those participants (n:99) who had medical records in the follow-up period were classified into 3 subgroups according to the time of presentation and follow-up visits (group-1: first admission and follow-up visit before the pandemic, group-2: first admission before the pandemic, the follow-up visit during the pandemic, group-3: first admission and follow-up visit during the pandemic). Results The age at presentation and age at pubertal onset were both significantly lower in the pandemic group than those in the pre-pandemic group(8.1 vs 8.6, p: < 0.001,7.7 vs 7.9,p:0.013, respectively). There was no significant difference between the body mass index standard deviation scores (BMI-SDS) values of the groups (0.57 vs 0.51, p:0.430). The initiation rate of pubertal suppression therapy at the time of presentation was significantly higher in the pandemic group compared to that of the pre-pandemic group (7.7%vs 27.5%), and in groups-2 & 3 compared to group-1, during follow-up (20%&44%vs 8%). Conclusion Our research showed that the onset of puberty occurred earlier in the pandemic period compared to the previous year, and the need for pubertal suppression therapy increased during the pandemic.